Implementasi Strategi Dinas Kesehatan dalam Mengatasi Peningkatan Kasus HIV di Kota Padang - Jannah, Raudhatul; Mubarak, Adil (Al-DYAS, 2025)
The high number of HIV cases in Padang City, despite the implementation of various policies and intervention programs, serves as the background for this study. The aim is to analyze the implementation of strategies by the Padang City Health Office in addressing the rise in HIV cases, based on Mayor Regulation No. 23 of 2018 on HIV and AIDS Control. This research employs a descriptive qualitative method, with data collected through in-depth interviews, documentation, and literature review. Informants include officials from the Health Office, community health center staff, and representatives from relevant NGOs. Data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing, with source triangulation to enhance validity. The findings indicate that the Health Office has implemented strategies through health promotion programs, Prevention of Sexual Transmission (PMTS), Voluntary Counseling and Testing (VCT) services, and adolescent education initiatives. However, the implementation of these policies has not been optimal due to limitations in human resources and funding, uneven communication, and bureaucratic complexity. Based on the policy implementation theory by Amir and George C. Edward III, it is found that successful implementation is influenced by communication, resources, implementers’ disposition, and bureaucratic structure. Therefore, strengthening strategies is essential through participatory communication, capacity building for health workers, bureaucratic streamlining, and the utilization of digital media and community-based approaches to enhance the effectiveness and sustainability of HIV/AIDS control programs in Padang City.